(untitled) (Medical Forum Monthly, 2024)
Objective: To study the association of BMI with blood glucose levels (FPG) and (RPG) in type 2 diabetes mellitus. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Ayub Medical Complex, Abbottabad. It was conducted from June 2014 to Feb 2015. Materials and Methods: The study involved 200 known type-2 diabetics, aged between 20 to 70 years. Both males and females were selected randomly. Questionnaire method was used to collect demographic and clinical data of participants. The fasting blood glucose profile was determined followed by two hours post-prandial blood glucose levels of each diabetic. Results: Statistical analysis was done using SPSS version 21. Mean ±SD, CV% were determined for BMI, fasting plasma glucose, random plasma glucose. Frequency distribution of above control measures was determined. Pearson’s correlation coefficient(r) was used to assess the association between above mentioned variables with Fasting plasma glucose and Random plasma glucose. Positive associations (p<0.005) were found for BMI. Non significant (p>0.005) association was seen in case of age; gender, for FPG. Poor glycemic levels were observed in case of our study subjects for FPG (139.3mg/dl) and RPG (207.6mg/dl). Conclusion: Poor glycemic control was observed incase of our study subjects, predisposing them to develop complications of diabetes. These associations can be used to effectively control diabetes and to implement their role in preventing complications of diabetes.